Probiotics and blood pressure: current insights - Upadrasta A; Madempudi RS (Dove Medical Press, 2016)
Aditya Upadrasta, Ratna Sudha Madempudi Centre for Research and Development, Unique Biotech Limited, Alexandria Knowledge Park, Shamirpet, Hyderabad, India Abstract: Gut microbiota play a significant role in host metabolic processes, and recent metagenomic surveys have revealed that they are involved in host immune modulation and influence host development and physiology (organ development). Initially, probiotics are identified as potential therapeutics to treat gastrointestinal disorders and to revitalize the disturbed gut ecosystem. Currently, studies are exploring the potential for expanded uses of probiotics for improving the health conditions in metabolic disorders that increase the risk of developing cardiovascular diseases such as hypertension. Further investigations are required to evaluate targeted and effective use of the wide variety of probiotic strains in various metabolic disorders to improve the overall health status of the host. This review addresses the causes of hypertension and the hypotensive effect of probiotics, with a focus on their mechanistic action. Keywords: probiotics, hypertension, ACE, gut microbiota, metabolic disorders, metagenomics